Exploring Surfaces of Revolution through GeoGebra: A Qualitative Approach to Calculus Teaching - Pimentel Paiva, Ana Carla; Vieira Alves, Francisco Regis; Barros de Campos, Helena Maria (Didactica Danubiensis, 2025)
This article presents a didactic approach to teaching surfaces of revolution in the Calculus of One Variable discipline, with an emphasis on the use of GeoGebra software as a visualization and graphical exploration tool. Visualization plays a fundamental role in understanding abstract mathematical concepts, and the use of interactive technologies can facilitate this process. The study includes essential mathematical definitions, a practical approach with proposed activities for using Geogebra and a discussion about its contribution to the teaching and learning of surfaces of revolution.